The daily life of nurses in pediatric oncology (Research, Society and Development, 2021)
Objectives: To assess the dimensions of action and affection in daily contact of nurses in pediatric oncology and discuss the implications of the dimensions action and affection in practice of nurses in pediatric oncology. Methods: Qualitative study light of the theoretical framework of Agnes Heller everyday. Study participants were 21 nurses selected by sampling technique Snowball. The data were produced by semi-structured interview mediated artistic production based on the technique of creativity and sensitivity and submitted to thematic analysis. Result: In the actions of the nurses are interpenetrated oncology specialty and children's particular circumstances. The affection dimension found up a slope, nurse protective attitude to the child and family on the rupture of ties and co-presence of death resulting in compassion. Conclusion: For the nurses daily contact in pediatric oncology was challenging and the potential proved limited due to the demand generated by emotional empathy and the personal involvement in assisting children and their families, creating professional wear and compassion fatigue.